Integracja edukacyjna z innej perspektywy - Dryżałowska, Grażyna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Educational Integration changed the social situation of persons with disability starting the sequence of new factors setting assessments for her. Getting to know their interrelationships and conditioning seems significant for current determining laying individuals of the disabled and wider social contexts in area which are accommodating oneself reasons for taking action ill-advised, in consequence faked, for their public integration.